Simultaneous production of L-lactic acid with high optical activity and a soil amendment with food waste that demonstrates plant growth promoting activity - Vichien, Kitpreechavanich; Arisa, Hayami; Anfal Talek; Fui, Clament Seung Chin; Yukihiro, Tashiro; Kenji, Sakai (Elsevier B.V., 2016)
A unique method to produce highly optically-active L-lactic acid and soil amendments that promote plant growth from food waste was proposed. Three Bacillus strains Bacillus subtilis KBKU21, B. subtilis N3-9 and Bacillus coagulans T27, were used. Strain KBKU21 accumulated 36.9 g/L L-lactic acid with 95.7% optical activity and 98.2% L-lactic acid selectivity when fermented at 43°C for 84 h in a model kitchen refuse (MKR) medium. Residual precipitate fraction (anaerobically-fermented MKR (AFM) compost) analysis revealed 4.60%, 0.70% and 0.75% of nitrogen (as N), phosphorous (as P2O5), and potassium (as K2O), respectively. Additionally, the carbon to nitrogen ratio decreased from 13.3 to 10.6. AFM compost with KBKU21 promoted plant growth parameters, including leaf length, plant height and fresh weight of Brassica rapa (Komatsuna), than that by chemical fertilizers or commercial compost. The concept provides an incentive for the complete recycling of food waste, contributing towards a sustainable production system.